Analysing space dependencies - Methods and factors for method development - de Sousa,Theodor (2022)
Vital societal functions and critical infrastructure rely to an increasing extent on services from space, such as navigation and positioning systems, timekeeping, and communications. However, understanding of space service dependencies is low among practitioners and society at large, with research on societal space dependency being limited as well. In order to avoid cascading effects from disruptions to these services, societal actors could benefit from conducting space service dependency analyses. The purpose of this thesis is to contribute towards the development of a method for such space dependency analyses, by identifying useful existing methods and important factors. Two studies have been conducted within the scope of this thesis. An explorative literature study covering twenty-one documents identified eight dependency analysis methods and fourteen factors deemed relevant for performing space service dependency analyses. In a semi-structured interview study with four participants, the findings from the literature study were validated and more perspectives on dependency analyses were provided along the themes of incentive, conduct, results and input data, as well as information security. Based on these studies, a prototype method has been developed, which together with the identified methods and factors are suggested to be implemented in future studies.
Keywords: Vital societal functions; critical infrastructure; interdependency; dependency analysis; space services; space infrastructure; GNSS; PNT; ICT; method development